Musculoskeletal symptoms in juvenile onset systemic lupus erythematosus - M. I. Kaleda; A. N. Arefieva; I. P. Nikishina (Современная ревматология, 2023)
In juvenile onset systemic lupus erythematosus (SLE), musculoskeletal involvement is one of the most common manifestations. Musculoskeletal symptoms may be due to disease activity itself, organ damage due to SLE activity, drug exposure, or comorbidities. Although they are not life-threatening, they still have a significant impact on disability severity and social exclusion. This article discusses the clinical features of various causes of musculoskeletal manifestations in SLE with onset in childhood and adolescence, the adequate interpretation of which is important for diagnosing and evaluating SLE activity and for correcting the treatment of the disease, thereby improving the long-term prognosis and quality of life of patients.